Understanding the implementation of 'Making Every Contact Count' (MECC) delivered by healthcare professionals in a mental health hospital: protocol for a pragmatic formative process evaluation. Issue 1 (31st December 2023) - Rodrigues, Angela M.; Kemp, Emma; Aquino, Maria Raisa Jessica; Wilson, Rob; Vasiljevic, Milica; McBride, Kate; Robson, Craig; Loraine, Mish; Harland, Jill; Haighton, Catherine
ABSTRACT: Background: 'Making Every Contact Count' (MECC) is a public health strategy supporting public-facing workers to use opportunities during routine contacts to enable health behaviour change. A mental health hospital in the North East of England is currently implementing a programme to embed MECC across the hospital supporting weight management ('A Weight Off Your Mind'). Bespoke MECC training has been developed to improve staff confidence in discussing physical activity, healthy eating, and related behaviour change with service users. This article describes the protocol for a pragmatic formative process evaluation to inform the implementation plan for MECC and facilitate successful implementation of the bespoke MECC training at scale. Methods/Design: An 18-month, mixed method pragmatic formative process evaluation, including qualitative research, surveys, document review and stakeholder engagement. This project is conducted within a mental health inpatient setting in the North East of England. Programme documents will be reviewed, mapped against MECC national guidelines, Behaviour Change Techniques (BCTs) and intervention functions within the Behaviour Change Wheel. A cross-sectional survey ( n = 365) and qualitative semi-structured interviews ( n = 30) will be conducted with healthcare practitioners delivering MECC to assess capability, opportunity and motivation. Data collection and fidelity procedures will be examined, including design, training and delivery dimensions of fidelity. Interviews with service users ( n = 20) will also be conducted. Discussion: Anticipated outcomes include developing recommendations to overcome barriers to delivery of and access to MECC, including whether to either support the use of the existing MECC protocol or tailor the MECC training programme. The findings are anticipated to improve fidelity of MECC training within mental health inpatient settings as well as provide evidence for MECC training at a national level. We also expect findings to influence strategic plans, policy, and practice specific to MECC and inform best practice in implementing wider brief intervention programmes.